Cellulose fiber composite resin composition, cellulose fiber composite resin molded article, and method for producing cellulose fiber composite resin composition
The cellulose fiber composite resin composition addresses aggregate formation issues by optimizing fiber content, size, and aspect ratio, enhancing mechanical strength and appearance through improved dispersion with a dispersant and low-molecular-weight resin.
Patent Information
- Application Number
- CN202380044428.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-05-29
- Publication Date
- 2024-12-27
AI Technical Summary
Existing cellulose fiber composite resins face issues with aggregate formation due to poor dispersion of hydrophilic cellulose fibers in lipophilic resins, leading to visible defects and reduced mechanical strength, especially when using high concentrations of cellulose fibers.
A cellulose fiber composite resin composition with a specific range of cellulose fiber content (50-90% by mass), average particle size (10-70 μm), and aspect ratio (5-100) is combined with a dispersant and a low-molecular-weight resin to suppress aggregate formation and enhance dispersion.
The composition achieves high mechanical strength and good appearance by preventing aggregate formation, suitable for applications requiring both mechanical integrity and aesthetic quality.
Smart Images

Figure CN119213068A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a cellulose fiber composite resin composition and a cellulose fiber composite resin formed body which is a formed body comprising the cellulose fiber composite resin composition. Background Art
[0002] So-called "common-purpose plastics" such as polyethylene (PE), polypropylene (PP), polystyrene (PS), and polyvinyl chloride (PVC) are relatively inexpensive, weigh a fraction of metal or ceramic, and are easily processed by molding. Consequently, these plastics are used as materials for a wide variety of daily necessities, including bags, packaging, containers, and sheet materials, as well as in industrial components such as automotive and electrical parts, daily necessities, and general merchandise.
[0003] However, general-purpose plastics have drawbacks such as insufficient mechanical strength. Consequently, the reality is that general-purpose plastics lack the properties required for materials used in various industrial products, including machinery such as automobiles and electrical, electronic, and information technology products, limiting their scope of application.
[0004] Meanwhile, so-called "engineering plastics" such as polyacetal (POM), polyamide (PA), polycarbonate (PC), and fluororesins offer excellent mechanical properties and are used in a variety of industrial products, including automobiles and other mechanical products, as well as electrical, electronic, and information technology products. However, engineering plastics are associated with high prices, difficulty in monomer recycling, and a significant environmental impact.
[0005] Therefore, there is a desire to significantly improve the material properties (mechanical strength, etc.) of general-purpose plastics. As a method for improving the material properties of general-purpose plastics, it is known to combine two or more resins or additives such as fillers to produce composite resins. In particular, to improve mechanical strength, fibrous fillers such as natural fibers, glass fibers, and carbon fibers are used. Among these, organic fibrous fillers such as cellulose have recently attracted attention as reinforcing fibers due to their low cost and excellent environmental performance when discarded.
[0006] One of the uses of composite resins is in components such as home appliance housings and automotive interior and exterior trim. Among these components, the presence of foreign matter in exterior parts directly visible to the human eye can result in a poor appearance and render the finished product unusable. When fillers are added to resins, since the fillers are a different material from the resin, particularly when combining hydrophilic fillers such as cellulose with highly lipophilic resins, the cellulose fibers may not disperse well in the resin, causing them to aggregate and form aggregates. Because the aggregates are larger than the individual fibers, they form aggregates (white or black spots) of a size that can be visually observed, resulting in poor appearance. Furthermore, since aggregates become the starting point for failure when stress loads are applied, suppressing aggregate formation is also important from the perspective of mechanical properties. Patent Document 1 describes suppressing aggregate formation and the generation of black spots caused by aggregates by controlling the size of dried cellulose fibers, the aggregation state of cellulose molecules, and the interactions between particles.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 2021-169577 Summary of the Invention
[0010] However, in the composite resin described in Patent Document 1, since a dried cellulose product containing large particles larger than 710 μm at a certain ratio is kneaded into the resin, there is a problem of these particles acting as starting points for agglomeration. Furthermore, since cellulose fibers are nanofibers and have a high aspect ratio, their surface area is large, making it difficult to add cellulose fibers at high concentrations.
[0011] The present application is an invention that solves the above-mentioned conventional problems, and an object of the invention is to provide a cellulose fiber composite resin composition that suppresses the generation of aggregates, has good appearance, and contains cellulose fibers at a high concentration.
[0012] The cellulose fiber composite resin composition of the present application comprises a main resin, cellulose fibers, and a dispersant. The cellulose fiber content is 50% to 90% by mass, the average particle size of the cellulose fibers is 10 μm to 70 μm, the proportion of cellulose fibers having a particle size of 710 μm or less is 95% or more, and the proportion of cellulose fibers having an aspect ratio of 5 to 100 is 95% or more. Here, aspect ratio is the ratio of the fiber length of the cellulose fibers to the fiber diameter of the cellulose fibers.
[0013] According to the cellulose fiber composite resin composition of the present application, even when cellulose fibers are composited in a high concentration of 50% by mass or more in a main resin, contact and entanglement between cellulose fibers can be suppressed, and generation of aggregates can be suppressed, resulting in a composite resin composition with good appearance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a schematic cross-sectional view showing the cross-sectional structure of a cellulose fiber composite resin formed body containing a cellulose fiber composite resin composition according to the first embodiment.
[0015] Figure 2 It is a figure which shows the conditions and measurement results of Examples 1-4 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0016] The first embodiment of the cellulose fiber composite resin composition comprises a main resin, cellulose fibers and a dispersant, wherein the content of the cellulose fibers is greater than 50% by mass and less than 90% by mass, the average particle size of the cellulose fibers is greater than 10 μm and less than 70 μm, the ratio of cellulose fibers with a particle size of less than 710 μm is greater than 95%, and the ratio of cellulose fibers with an aspect ratio (fiber length / fiber diameter) of greater than 5 and less than 100 is greater than 95%.
[0017] The cellulose fiber composite resin composition of the second embodiment may be the composition according to the first embodiment, wherein the ratio of cellulose fibers bent at 90° or more among the cellulose fibers is 30% or less.
[0018] The cellulose fiber composite resin composition of the third embodiment may be the cellulose fiber composite resin composition according to the first embodiment, further comprising a low molecular weight resin having a molecular weight of 1,000 to 50,000.
[0019] A fourth embodiment of the cellulose fiber composite resin composition may be the third embodiment, wherein the low-molecular weight resin accounts for 0.5% by mass to 20% by mass relative to 100% by mass of the cellulose fibers.
[0020] The cellulose fiber composite resin molded article of the fifth embodiment is a molded article comprising the cellulose fiber composite resin composition of any one of the first to fourth embodiments.
[0021] The cellulose fiber composite resin formed body of the sixth embodiment may be one in which the fiber length direction of more than 70% of the cellulose fibers in the epidermis layer on the surface of the cellulose fiber composite resin formed body is oriented at an angle of more than 0° and within 30° relative to the surface of the cellulose fiber composite resin formed body.
[0022] The seventh embodiment of the method for producing a cellulose fiber composite resin composition includes a preparation step of preparing a base resin, cellulose fibers, and a dispersant, and a kneading step of kneading the base resin, cellulose fibers, and dispersant to obtain the cellulose fiber composite resin composition.
[0023] The eighth embodiment of the method for producing a cellulose-fiber composite resin composition may be the method according to the seventh embodiment, further comprising a mixing step for causing a powdered or liquid additional resin to adhere to the cellulose fibers.
[0024] A ninth aspect of the method for producing a cellulose-fiber composite resin composition may be the method according to the eighth aspect, wherein the added resin is a powdered resin having an average particle size of 100 μm to 1000 μm.
[0025] Hereinafter, a cellulose fiber composite resin composition and a cellulose fiber composite resin molded article including the composition according to an embodiment will be described with reference to the accompanying drawings. In the following description, identical components are denoted by identical reference numerals, and description thereof will be omitted as appropriate.
[0026] (Implementation Method 1)
[0027] <Cellulose fiber composite resin composition and molded article>
[0028] Figure 1 This is a schematic cross-sectional view showing the cross-sectional structure of a cellulose-fiber-composite-resin molded body 10 containing a cellulose-fiber-composite-resin composition according to the first embodiment.
[0029] The cellulose fiber composite resin composition contained in the cellulose fiber composite resin molded body 10 of the first embodiment comprises a main resin 1, cellulose fibers 2, a dispersant 3, and a low molecular weight resin 4. The cellulose fiber composite resin composition is as follows: Figure 1 As shown, cellulose fibers 2, dispersant 3, and low-molecular-weight resin 4 are dispersed in the matrix of the main resin 1. The dispersant 3 is present at the interface between the cellulose fibers 2 and the main resin 1. The low-molecular-weight resin 4 is mainly present around the cellulose fibers 2. Figure 1 As shown, the cellulose fiber composite resin molded body 10 is roughly composed of two layers: a skin layer 11 on the surface and a core layer 12 inside. When the molten resin enters the mold during molding, the resin surface in contact with the mold surface is rapidly cooled, and the resin inside is slowly cooled. Since the cooling rate is different on the surface and inside, the properties such as the degree of crystallization are different, and the skin layer 11 on the resin surface and the core layer 12 inside the resin can be distinguished by microscopic observation. In this specification, the layer on the surface of the molded body that is rapidly cooled during molding is defined as the skin layer 11, and the layer inside the molded body that is slowly cooled during molding is defined as the core layer 12.
[0030] Hereinafter, each member constituting the cellulose-fiber-composite-resin composition contained in the cellulose-fiber-composite-resin molded body 10 will be described.
[0031] <Main resin>
[0032] The main resin 1 of Embodiment 1 is preferably a thermoplastic resin to ensure good moldability. Examples of thermoplastic resins include olefin resins (including cyclic olefin resins), styrene resins, (meth)acrylic resins, organic acid vinyl ester resins or their derivatives, vinyl ether resins, halogen composite resins, polycarbonate resins, polyester resins, polyamide resins, thermoplastic polyurethane resins, polysulfone resins (polyethersulfone, polysulfone, etc.), polyphenylene ether resins (polymers of 2,6-xylenol, etc.), cellulose derivatives (cellulose esters, cellulose carbamates, cellulose ethers, etc.), silicone resins (polydimethylsiloxane, polymethylphenylsiloxane, etc.), rubbers or elastomers (diene rubbers such as polybutadiene and polyisoprene, styrene-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylic rubbers, polyurethane rubbers, silicone rubbers, etc.). The above resins can be used alone or in combination of two or more. It should be noted that the main resin 1 is not limited to the above materials as long as it has thermoplastic properties.
[0033] Among these thermoplastic resins, the main resin 1 is preferably an olefin resin with a relatively low melting point. As olefin resins, in addition to homopolymers of olefin monomers, copolymers of olefin monomers and copolymers of olefin monomers with other copolymerizable monomers are also included. Examples of olefin monomers include chain olefins (α-C2-20 olefins such as ethylene, propylene, 1-butene, isobutylene, 1-pentene, 4-methyl-1-pentene, 1-octene, etc.), cyclic olefins, etc. These olefin monomers can be used alone or in combination of two or more. Among the above-mentioned olefin monomers, chain olefins such as ethylene and propylene are preferred. Other copolymerizable monomers include, for example, fatty acid vinyl esters such as vinyl acetate and vinyl propionate; (meth)acrylic acid monomers such as (meth)acrylic acid, alkyl (meth)acrylates, and glycidyl (meth)acrylate; unsaturated dicarboxylic acids or their anhydrides such as maleic acid, fumaric acid, and maleic anhydride; vinyl esters of carboxylic acids (such as vinyl acetate and vinyl propionate); cyclic olefins such as norbornene and cyclopentadiene; and dienes such as butadiene and isoprene. These copolymerizable monomers can be used alone or in combination of two or more. Specific examples of olefin-based resins include copolymers of chain olefins (particularly α-C2-4 olefins) such as polyethylene (low-density, medium-density, high-density, or linear low-density polyethylene), polypropylene, ethylene-propylene copolymers, and terpolymers such as ethylene-propylene-butene-1.
[0034] Cellulose fiber
[0035] Examples of the cellulose fibers 2 in the first embodiment include cellulose fibers and lignocellulosic fibers. Examples of raw materials for cellulose fibers and lignocellulosic fibers include natural materials such as wood (coniferous and broadleaved trees), cotton linters, kenaf, abaca, sisal, jute, Indian grass, Spanish grass, bagasse, rice straw, wheat straw, reeds, and bamboo. Alternatively, modified cellulose fibers with surface and terminal chemical modifications such as acid, amine, and epoxy groups may be used. Among these cellulose fibers, cellulose fibers made from pulp are preferred as cellulose fibers 2. Cellulose fibers from which impurities such as lignin and hemicellulose have been removed and from which the cellulose content is 70% or greater are preferably used, but are not limited to pulp.
[0036] Dispersants
[0037] Examples of the dispersant 3 in the first embodiment include various titanate coupling agents, silane coupling agents, unsaturated carboxylic acids, maleic acid, maleic anhydride, modified polyolefins grafted with such anhydrides, fatty acids, fatty acid metal salts, and fatty acid esters. The silane coupling agents are preferably unsaturated hydrocarbon or epoxy silane coupling agents. The surface of the dispersant can be treated or modified with a thermosetting or thermoplastic polymer component. The dispersant 3 can be appropriately selected based on the combination of the main resin 1 and the cellulose fiber 2.
[0038] <Low molecular weight resin>
[0039] As the low-molecular-weight resin 4, a thermoplastic resin is preferably used because it needs to be melted during kneading. Examples of thermoplastic resins include olefin resins (including cyclic olefin resins), styrene resins, (meth)acrylic resins, organic acid vinyl ester resins or their derivatives, vinyl ether resins, halogen composite resins, polycarbonate resins, polyester resins, polyamide resins, thermoplastic polyurethane resins, polysulfone resins (polyethersulfone, polysulfone, etc.), polyphenylene ether resins (polymers of 2,6-xylenol, etc.), cellulose derivatives (cellulose esters, cellulose carbamates, cellulose ethers, etc.), silicone resins (polydimethylsiloxane, polymethylphenylsiloxane, etc.), rubbers or elastomers (diene rubbers such as polybutadiene and polyisoprene, styrene-butadiene copolymers, acrylonitrile-butadiene copolymers, acrylic rubbers, polyurethane rubbers, silicone rubbers, etc.), waxes, etc. The above resins can be used alone or in combination of two or more. It should be noted that the low-molecular-weight resin 4 is not limited to the above materials as long as it has thermoplastic properties.
[0040] The cellulose fiber composite resin composition of the first embodiment comprises a main resin, cellulose fibers, and a dispersant. The cellulose fiber content is 50% to 90% by mass, the average cellulose fiber particle size is 10 μm to 70 μm, the proportion of cellulose fibers with a particle size of 710 μm or less is 95% or more, and the proportion of cellulose fibers with an aspect ratio (fiber length / fiber diameter) of 5 to 100 is 95% or more. More specifically, the cellulose fiber content in the cellulose fiber composite resin composition is 50% to 90% by mass. Of the total cellulose fibers, the proportion of cellulose fibers with a particle size of 710 μm or less is 95% or more. Of the total cellulose fibers, the proportion of cellulose fibers with an aspect ratio of 5 to 100 is 95% or more. Here, the aspect ratio of the cellulose fibers is the ratio of the fiber length of the cellulose fibers to the fiber diameter of the cellulose fibers (fiber length / fiber diameter). Fiber length refers to the length of the fiber, and fiber diameter refers to the diameter of the fiber. When the average particle size is less than 10 μm, the reinforcing effect based on the cellulose fibers becomes smaller and the mechanical properties of the composite resin become lower. When the average particle size is greater than 70 μm, the cellulose fibers are easy to contact each other and are easy to form agglomerates. That is, when the average particle size of the cellulose fibers is less than 70 μm, the formation of agglomerates of the cellulose fibers can be suppressed. It should be noted that the average particle size of the cellulose fibers can also be greater than 10 μm and less than 50 μm. In addition, when the aspect ratio is less than 5, the cellulose fibers become particulate and are easy to agglomerate. On the other hand, when the aspect ratio is greater than 100, the fibers become very long, so the fibers are easy to entangle with each other and are easy to form agglomerates. Therefore, the average particle size, particle size, and aspect ratio of the cellulose fibers are preferably within the above ranges.
[0041] The average particle size of cellulose fibers can be measured using methods such as the sieving method (JIS K 0069:1992), the laser diffraction / scattering method (JIS Z 8825:2013), and the dynamic light scattering method (JIS Z 8828:2013). Specifically, the average particle size of cellulose fibers can be measured using a particle size distribution analyzer. In the sieving method, sieving is performed using multiple sieves of varying mesh sizes, and the particle size distribution is determined based on the weight of the residue on each sieve. In the laser diffraction / scattering method, laser light is irradiated onto particles in a liquid or gas, and the particle size is measured based on the fact that the intensity pattern of the scattered light from the particles depends on the particle size. In the laser diffraction / scattering method, the particle size is measured as the equivalent sphere diameter. In the dynamic light scattering method, the particle size is measured based on the Brownian motion of particles suspended in a liquid. Specifically, the phase shift between the scattered light and the incident light caused by the Brownian motion is observed, and the particle size is calculated based on the observed phase shift.
[0042] In addition, as the average particle size, for example, the median particle size D at which the cumulative frequency in the obtained particle size distribution reaches 50% can be used. 50 The above average particle size uses the median particle size D 50 express.
[0043] The aspect ratio of cellulose fibers can be measured using, for example, a scanning electron microscope (SEM).
[0044] The cellulose fibers 2 of the first embodiment preferably have a ratio of 30% or less of cellulose fibers bent at 90° or more. If the ratio of cellulose fibers bent at 90° or more exceeds 30%, the bent cellulose fibers tend to contact and become entangled, thus easily forming aggregates. Therefore, the ratio of cellulose fibers bent at 90° or more is preferably within the above range.
[0045] Among the cellulose fibers in the cellulose fiber composite resin molded body of the present embodiment 1, preferably more than 80% and more preferably more than 90% of the cellulose fibers in the epidermis layer on the surface of the composite resin molded body are oriented at an angle θ of 0° or more and within 30° relative to the surface of the composite resin molded body in the fiber length direction. Since the epidermis layer is located on the outermost surface of the molded body, it has a particularly large impact on the appearance. By orienting the cellulose fibers in the epidermis layer parallel to the epidermis layer, the contact between the cellulose fibers is suppressed and the formation of agglomerates is suppressed. On the other hand, when the ratio of orientation at an angle θ of 0° or more and within 30° is less than 80%, the orientation of the cellulose fibers in the epidermis layer becomes random, the entanglement between the cellulose fibers increases, and agglomerates are formed. Therefore, the ratio of the cellulose fibers in the epidermis layer oriented at an angle of 0° or more and within 30° in the fiber length direction is preferably within the above range.
[0046] The molecular weight of the low-molecular-weight resin 4 of the composite resin molded article of this embodiment 1 is preferably 1,000 to 50,000, more preferably 3,000 to 30,000. When the molecular weight is less than 1,000, the strength of the resin alone is weak, significantly reducing the overall strength of the composite resin. When the molecular weight is greater than 50,000, the viscosity of the resin alone increases, making it difficult for the resin to enter the defibration section of the cellulose fibers, and thus reducing the effectiveness of suppressing the formation of aggregates. Therefore, the molecular weight of the low-molecular-weight resin 4 is preferably within the above range.
[0047] Regarding the addition amount of the above-mentioned low-molecular-weight resin 4, relative to 100 mass % of the above-mentioned cellulose fibers, it is preferably 0.5 mass % or more and 20 mass % or less, and more preferably 1.0 mass % or more and 10 mass % or less. When the addition amount of the low-molecular-weight resin 4 is less than 0.5 mass %, since the amount of the resin is too little, it is impossible to suppress the contact between the cellulose fibers and the generation of agglomerates. In addition, it is impossible to improve the fluidity of the cellulose fibers. When it is greater than 20 mass %, since the amount of the low-molecular-weight resin is large relative to the cellulose fibers, it is impossible to fully exert the reinforcing effect. Therefore, the addition amount of the above-mentioned low-molecular-weight resin 4 is preferably within the above-mentioned range.
[0048] <Method for producing cellulose fiber composite resin composition>
[0049] The method for producing a cellulose fiber composite resin according to the first embodiment includes a preparation step of preparing a base resin, cellulose fibers, and a dispersant, and a kneading step of kneading the base resin, cellulose fibers, and dispersant to obtain a cellulose fiber composite resin composition.
[0050] In addition, a mixing process for attaching a powder or liquid low-molecular resin to the cellulose fibers 2 may be further included. Before the above-mentioned mixing process, the powder or liquid low-molecular resin is attached to the surface of the cellulose fibers, thereby making it difficult for the cellulose fibers to directly contact each other, and thus the coagulation of the cellulose fibers can be suppressed. If the generation of the coagulations before mixing can be suppressed, the generation of the coagulations of the cellulose fibers in the composite resin after mixing can also be suppressed. When using resin particles, since the size is significantly larger than the cellulose fibers, even if the resin particles and the cellulose fibers are mixed, they will be separated into each component, thereby being unable to suppress the coagulation of the cellulose fibers. Therefore, it is preferred that the above-mentioned low-molecular resin 4 is a powder or liquid, and a mixing process is performed before the mixing process.
[0051] When the above-mentioned low-molecular-weight resin 4 is a powdered resin, its average particle size is preferably greater than 100 μm and less than 1000 μm, and more preferably greater than 200 μm and less than 500 μm. When the average particle size of the powdered resin is less than 100 μm, since the difference with the average particle size of the cellulose fiber is small, even if the powdered resin adheres to the surface of the cellulose fiber, it cannot be prevented from contacting with other cellulose fibers, and the generation of agglomerates before kneading cannot be suppressed. In addition, when the average particle size of the powdered resin is greater than 1000 μm, since the surface area of the powdered resin becomes smaller, the aggregation suppression effect of the cellulose fiber per unit mass becomes smaller. In addition, it is difficult to mix the cellulose fiber and the powdered resin uniformly. Therefore, the average particle size of the powdered resin of the above-mentioned low-molecular-weight resin 4 is preferably within the above-mentioned range.
[0052] As the mixing device used in the method for producing the cellulose fiber composite resin composition of the present embodiment 1, a single screw mixer, a twin screw mixer, a roll mixer, a kneader, a Banbury mixer and a combination thereof can be cited. From the viewpoint of being easy to apply high shear and high in mass production, a continuous twin screw mixer and a continuous roll mixer are preferred. As long as it is a method that can apply high shear stress, a mixing method other than the above may also be used. In addition, since cellulose fibers are prone to degradation caused by heat, it is preferably mixed at low temperatures as much as possible.
[0053] The cellulose fiber composite resin composition extruded from the kneading device is cut into pellets by a pelletizer or other cutting process. Pelletization methods include in-flight heat cutting, underwater heat cutting, and strand cutting, which are performed immediately after the resin is melted. Alternatively, there is a pulverization method, which involves first forming a molded body or sheet and then pulverizing and cutting the resulting pellets.
[0054] <Method for producing cellulose fiber composite resin molded body>
[0055] The pellets of the cellulose fiber composite resin composition are melted and injection-molded into a mold to produce an injection-molded article as a cellulose fiber composite resin molded body.
[0056] Hereinafter, examples and comparative examples obtained from experiments conducted by the inventors will be described.
[0057] Example
[0058] Figure 2 The conditions and measurement results of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in FIG.
[0059] The cellulose fiber composite resin composition was produced by the following production method: As described above, the kneading apparatus may be a single-screw kneader, a twin-screw kneader, a roll kneader, a kneader, a Banbury mixer, or a combination thereof. In the examples, a twin-screw kneader was used.
[0060] Polypropylene (J108M, manufactured by Prime Polymer Co., Ltd.), pulverized pulp (cellulose fiber), maleic anhydride-modified polypropylene (Umex, manufactured by Sanyo Chemical Industries, Ltd.) as a dispersant, and a low-molecular-weight polyolefin (HI-WAX, manufactured by Mitsui Chemicals, Inc.) as a low-molecular-weight resin were weighed at a mass ratio of 33:60:3:3. A mixture of the main resin and the dispersant, and a mixture of the pulverized pulp and the low-molecular-weight resin were fed to a kneader, respectively. Hardwood pulp (Mitsubishi Kitakami LBKP, manufactured by Mitsubishi Paper Industries, Ltd.) was used as the starting material for the pulverized pulp. This pulp was pulverized in a pulverizer to obtain pulverized pulp. The pulverization process adjusted the size of the cellulose fibers and other factors. Dry pulverization is preferred because wet pulverization requires a drying step after pulverization, and agglomeration occurs during drying. Sieving was used to measure the average particle size of the cellulose fibers.
[0061] Melt-kneading and dispersion were performed using a twin-screw kneader (KRC kneader manufactured by Kurimoto Iron Works Co., Ltd.). The shear force can be varied by changing the screw configuration of the twin-screw kneader; in Example 1, a low-shear type was used. The composite resin discharged from the twin-screw kneader was hot-cut to produce cellulose fiber composite resin pellets.
[0062] The cellulose fiber composite resin pellets were used to produce composite resin molded body test pieces using an injection molding machine (180AD, manufactured by Nippon Steel Works). The dumbbell test pieces were produced under the following conditions: a resin temperature of 200°C, a mold temperature of 40°C, an injection speed of 60 mm / s, and a holding pressure of 100 MPa. The pellets were fed into the molding machine's screw via a hopper, and the penetration rate was measured based on the reduction in pellets per unit time, confirming that the pellets remained constant. The shape of the test piece was varied according to the evaluation criteria described below. For elastic modulus measurements, size 1 dumbbell test pieces were produced. For appearance (agglomerates), 2 mm² flat plate test pieces measuring 60 mm x 70 mm were produced. The resulting cellulose fiber composite resin molded body test pieces were evaluated using the following method.
[0063] [Evaluation Items for Composite Resin Molded Articles]
[0064] (Elastic modulus of composite resin molded article)
[0065] A three-point bending test was performed using the resulting dumbbell-shaped No. 1 test piece. The elastic modulus was evaluated by marking a value of x for test pieces less than 3.0 GPa, a value of 3.0 GPa to less than 3.5 GPa to △, a value of 3.5 GPa to less than 5.0 GPa to ◯, and a value of 5.0 GPa or more to ◎. The elastic modulus of this test piece was 5.8 GPa, resulting in a ◎ rating.
[0066] (Appearance of Composite Resin Molded Articles)
[0067] The resulting flat test piece was used to visually evaluate the appearance of the composite resin molded article. A score of × was assigned if three or more agglomerates were visually observed in a 60 mm x 70 mm area of the flat test piece; a score of △ was assigned if one to two agglomerates were observed; and a score of ○ was assigned if no agglomerates were observed. A score of ○ was assigned if no agglomerates were visually observed in the test piece.
[0068] (Evaluation of Curvature of Cellulose Fibers in Composite Resin Molded Articles)
[0069] A portion of the resulting dumbbell-shaped test piece No. 1 was cut out and observed under a SEM. A score of × was assigned if the ratio of cellulose fibers bent 90° or more in the resin was 30% or more, a score of ○ was assigned if it was 20% or more but less than 30%, and a score of ◎ was assigned if it was less than 20%. The ratio of cellulose fibers bent 90° or more in this test piece was 16%, resulting in a score of ◎.
[0070] (Orientation of fibers in the epidermis)
[0071] A portion of the resulting dumbbell-shaped test piece No. 1 was cut out and subjected to cross-sectional polarization microscopy. The resulting polarization microscopy image was used to measure the longitudinal angle of the cellulose fibers in the epidermal layer, with the test piece surface at 0°. A value of × was assigned if the ratio of cellulose fibers with longitudinal angles of 0° or greater and within 30° relative to the surface was less than 50%. A value of △ was assigned if the ratio was between 50% and less than 70%, and a value of ○ was assigned if the ratio was 70% or greater.
[0072] The ratio of the cellulose fibers in the test piece at an angle of 0° or more and within 30° was 84%, and the evaluation was ○.
[0073] (Example 2)
[0074] In Example 2, no low-molecular-weight resin was used, and the mass ratio of main resin: cellulose fiber: dispersant: low-molecular-weight resin was changed to 37:60:3:0. Cellulose fiber composite resin particles and molded articles were produced under the same conditions as in Example 1. Evaluations were also conducted in the same manner as in Example 1.
[0075] (Example 3)
[0076] In Example 3, pulverized pulp with a larger average particle size and aspect ratio than in Example 1 was used as the cellulose fiber. Other material and process conditions were the same as in Example 1 to produce cellulose fiber composite resin particles and a molded article. Evaluations were also conducted in the same manner as in Example 1.
[0077] (Example 4)
[0078] In Example 4, cellulose fibers were prepared by mixing 95% by mass of the powder pulp used in Example 1 with 5% by mass of a powder pulp having an average particle size of 20 μm and an aspect ratio of 5. Other material and process conditions were the same as in Example 1 to produce cellulose fiber composite resin particles and a molded article. Evaluations were also conducted in the same manner as in Example 1.
[0079] (Comparative Example 1)
[0080] In Comparative Example 1, the mass ratio of main resin: pulverized pulp: dispersant was changed to 88:10:2. Other material and process conditions were the same as in Example 1 to produce composite resin particles and a molded article. Evaluations were also conducted in the same manner as in Example 1.
[0081] (Comparative Example 2)
[0082] In Comparative Example 2, pulverized pulp with an average particle size of 350 μm, which is larger than that in Example 1, was used as the cellulose fiber. The other material and process conditions were the same as in Example 1 to produce composite resin particles and a molded article. The same evaluations as in Example 1 were also performed.
[0083] (Comparative Example 3)
[0084] In Comparative Example 3, pulverized pulp with a higher ratio of particles with a diameter of 710 μm than in Example 1 was used as the cellulose fiber. Other material and process conditions were the same as in Example 1 to produce cellulose fiber composite resin particles and a molded article. Evaluations were also conducted in the same manner as in Example 1.
[0085] (Comparative Example 4)
[0086] In Comparative Example 4, pulverized pulp with a larger aspect ratio of 150 than in Example 1 was used as the cellulose fiber. Other material and process conditions were the same as in Example 1 to produce plant fiber composite resin particles and a molded article. Evaluations were also conducted in the same manner as in Example 1.
[0087] The measurement results of Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Figure 2 in the table.
[0088] In Example 2, which did not use a low-molecular-weight resin, the cellulose fiber had lower fluidity than in Example 1, so the rate of cellulose fiber bending at 90° or greater was 23%, resulting in an evaluation of ○. On the other hand, the absence of a low-molecular-weight resin component with low mechanical properties resulted in an elastic modulus of 6.0 GPa.
[0089] In Example 3, which used pulverized pulp with an average particle size of 62 μm and an aspect ratio of 46, the particle size was not significantly increased compared to Example 1, and the aspect ratio was increased, so the reinforcement effect was enhanced, and the elastic modulus was 6.2 GPa, resulting in an evaluation result of ◎.
[0090] In Example 4 using two types of ground pulp, the elastic modulus decreased to 5.6 GPa because the ratio of cellulose fibers having a small particle size and aspect ratio increased.
[0091] In Comparative Example 1, in which the mass ratio of cellulose fibers to the total raw materials was reduced, the reinforcing effect of the filler on the composite resin was small due to the small amount of cellulose fibers, resulting in an elastic modulus of 1.8 GPa and an evaluation result of ×.
[0092] In Comparative Example 2 using cellulose fibers having a large average particle size, the number of generated aggregates increased due to contact between the cellulose fibers, and thus the evaluation result was x.
[0093] In Comparative Example 3 using cellulose fibers having a high ratio of 710 μm particle size, the amount of aggregates generated was large, mainly due to the cellulose fibers having a large particle size, and therefore the evaluation result was x.
[0094] In Comparative Example 4 using cellulose fibers with a large aspect ratio, the high aspect ratio increased the ratio of the bent portion of the cellulose fibers, resulting in increased contact and entanglement between fibers and an increase in the number of aggregates. Therefore, the evaluation result was x.
[0095] The above evaluation shows that when the cellulose fiber content is less than 50% by mass, the composite resin strength does not reach the required level. On the other hand, when using cellulose fibers with an average particle size of 50 μm or greater, when using cellulose fibers with a particle size of 710 μm or less comprising less than 95% of the fibers, and when using cellulose fibers with an aspect ratio of 100 or greater, entanglement between the cellulose fibers increases, making it impossible to suppress the formation of aggregates.
[0096] Based on the above results, it can be seen that by including a main resin, cellulose fibers, and a dispersant, the content of the above-mentioned cellulose fibers is greater than 50 mass% and less than 90 mass%, the average particle size of the above-mentioned cellulose fibers is greater than 10 μm and less than 50 μm, the ratio of cellulose fibers with a particle size of less than 710 μm is greater than 95%, and the aspect ratio (fiber length / fiber diameter) is greater than 5 and less than 100, so that the cellulose fiber composite resin composition can suppress the formation of agglomerates, has good appearance, and has higher mechanical strength.
[0097] Industrial applicability
[0098] The cellulose fiber composite resin composition of the present application can provide a molded article having superior mechanical strength compared to conventional general-purpose resins, and having a good appearance without the appearance defects such as white spots and black spots caused by cellulose fiber aggregates. The cellulose fiber composite resin molded article of the present application can be used in exterior parts for home appliance housings, building materials, and automotive components, etc., which require both excellent mechanical strength and good appearance.
[0099] Description of Reference Numerals
[0100] 1 Main resin, 2 Cellulose fiber, 3 Dispersant, 4 Low molecular weight resin, 10 Cellulose fiber composite resin molded body, 11 Skin layer, 12 Core layer.
Claims
1. A cellulose fiber composite resin composition comprising a main resin, cellulose fibers and a dispersant, The cellulose fiber content is 50% by mass or more and 90% by mass or less, The average particle size of the cellulose fibers is 10 μm or more and 70 μm or less. Among the cellulose fibers, the ratio of cellulose fibers having a particle size of 710 μm or less is 95% or more, Among the cellulose fibers, the ratio of cellulose fibers having an aspect ratio of 5 or more and 100 or less, the aspect ratio being a ratio of a fiber length of the cellulose fibers to a fiber diameter of the cellulose fibers, is 95% or more.
2. The cellulose fiber composite resin composition according to claim 1, wherein Among the cellulose fibers, the ratio of the cellulose fibers bent at 90° or more is 30% or less. 3 . The cellulose fiber composite resin composition according to claim 1 , further comprising a low molecular weight resin having a molecular weight of 1,000 or more and 50,000 or less.
4. The cellulose fiber composite resin composition according to claim 3, wherein The low-molecular-weight resin accounts for 0.5% by mass or more and 20% by mass or less relative to 100% by mass of the cellulose fibers. 5 . A cellulose fiber composite resin formed body comprising the cellulose fiber composite resin composition according to claim 1 .
6. The cellulose fiber composite resin formed body according to claim 5, wherein In the skin layer including the surface of the cellulose fiber composite resin formed body, 70% or more of the cellulose fibers have their fiber length directions oriented at an angle of 0° or more and within 30° with respect to the surface of the cellulose fiber composite resin formed body.
7. A method for producing a cellulose fiber composite resin composition, the method comprising: Preparation process, preparing main agent resin, cellulose fiber and dispersant; as well as The kneading step is to knead the main component resin, the cellulose fibers, and the dispersant to obtain a cellulose fiber composite resin composition. 8 . The method for producing a cellulose fiber composite resin composition according to claim 7 , further comprising a mixing step for causing a powder or liquid additional resin to adhere to the cellulose fibers.
9. The method for producing a cellulose fiber composite resin composition according to claim 8, wherein The added resin is a powder resin having an average particle size of 100 μm or more and 1000 μm or less.
Citation Information
Patent Citations
Dried cellulose fiber and method for producing the same, and method for producing resin composite
JP2021169577A
